2019
DOI: 10.1021/acsnano.8b06655
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, Temporal, and Dose Control of Drug Delivery using Noninvasive Magnetic Stimulation

Abstract: Noninvasive stimuli-responsive drug delivery using magnetic fields in conjunction with superparamagnetic nanoparticles offers the potential for the spatial and temporal control of drug release. When hyperthermia is not desired and control of the dosage is required, it is necessary to design a platform in which local heating on the nanoscale releases the therapeutic cargo without the bulk heating of the surrounding medium. In this paper, we report a design using a stimuli-responsive nanoparticle platform to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 83 publications
(135 reference statements)
2
102
0
Order By: Relevance
“…However, ultrasound signal can be influenced by air attenuation and bone structure. Magnetic responsive nanoparticles exhibit broader application such as in respiratory system which is filled with air and central nervous system covered with cranial bone [143]. Furthermore, magnetic responsive nanoparticles can help spatially and temporally localize actives without restriction by tissues depth [143].…”
Section: -1000nm 12 Daysmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ultrasound signal can be influenced by air attenuation and bone structure. Magnetic responsive nanoparticles exhibit broader application such as in respiratory system which is filled with air and central nervous system covered with cranial bone [143]. Furthermore, magnetic responsive nanoparticles can help spatially and temporally localize actives without restriction by tissues depth [143].…”
Section: -1000nm 12 Daysmentioning
confidence: 99%
“…Magnetic responsive nanoparticles exhibit broader application such as in respiratory system which is filled with air and central nervous system covered with cranial bone [143]. Furthermore, magnetic responsive nanoparticles can help spatially and temporally localize actives without restriction by tissues depth [143]. Generally, there are three mechanisms underlying magnetic response, which are magnetic deformation, magnetic guidance, and magnetic-induced hyperthermia [144,145].…”
Section: -1000nm 12 Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…External stimuli such as ultrasounds, light or magnetic fields, are powerful, versatile external triggers to achieve spatiotemporal‐controlled drug delivery from artificial carriers in living systems 17. Such stimuli have been typically used to promote intracellular delivery of small molecules such anticancer drugs from plasmonic,18 magnetic,19 and ultrasound‐sensitive20 carriers. Examples of external‐stimulus‐controlled delivery of large macromolecules such as proteins (e.g., Abs), however, are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the combination of chemotherapy and thermal treatment, enhances treatment efficacy [24,25]. Notably, magnetic nanoparticles and anticancer drug-loaded materials can be used in a way to exploit the heat generated by magnetic nanoparticles in response to alternating magnetic field (AMF) exposure [26][27][28][29], which can subsequently act as a trigger for releasing drugs from the materials, achieving a remotely controllable on-demand administration of combined chemotherapy and thermal treatment [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%